Energy balance of a low energy house - Džiugaitė-Tumėnienė, Rasa; Jankauskas, Vidmantas; Motuzienė, Violeta (Journal of Civil Engineering and Management, 2012)
Currently, such topics as improvement of energy efficiency of buildings and energy systems, development of sustainable building concepts, and promotion of renewable energy sources are in the focus of attention. The energy efficiency targets of the European Union are based on information regarding energy consumed by buildings. The amount of energy consumed by buildings depends on the main influencing factors (namely, climate parameters, building envelope, energy systems, building operation and maintenance, activities and behaviour of occupants), which have to be considered in order to identify energy efficiency potentials and opportunities. The article aims to investigate the total amount of energy consumed by a low energy house, built in Lithuania, using a combination of energy consumption data received from a simulation and measured energy consumption data. The energy performance analysis in the low energy house revealed some factors that have the main influence on the total figures of energy consumed by the house. The identified significant factors were used to find the optimal solutions for the design of low energy buildings.